Penerapan Algoritma K-Means dalam Proses Clustering Penilaian Kinerja Aparatur Sipil Negera di Sekretariat DPRD Pematangsiantar - Aulia, Della; Safii, M; Suhendro, Dedi (STIKOM Tunas Bangsa Pematangsiantar, 2021)
This study discusses the assessment of the performance of the ASN (State Civil Apparatus) in the Pematangsiantar DPRD Secretariat based on the quality of its work. In carrying out their performance, emoployess are still often truant and have a poor work ethic.In this case the research aims to improve employee welfare. During this time the amount of employee income is only based on the group and position they have. This study uses the K-Means method to classify or classify employee performance quality assessments based on SKP (employee work objectives) with additional income based on work quality assessment and employee behavior.After conducting this research there is a result that in carrying out the performance of employees include Quality, Quantity, Time, Cost of each task activity so as to produce a system capable of assisting the appraisal officer in evaluating the quality of employee performance using the K-Means algorithm as information to find out the employee including very good, enough, and less.